Bauman's Challenge
XII, 213 p.
Keywords: This unique and original collection by internationally renowned scholars uses critical engagements with Zygmunt Bauman's sociology to understand the challenges that face globalized human societies at the start of the 21st century. Includes a concluding chapter by Bauman.